Implementation of Combination RSA, Vigenere Cipher, and Permutation Cipher in Digital Communication - Tielung, M. Fariel Fahriza; Kurniadi, Edi; Sylviani, Sisilia (Lembaga Penelitian dan Pengembangan Matematika dan Statistika Terapan Indonesia, PT Anugrah Teknologi Kecerdasan Buatan PT Anugrah Teknologi Kecerdasan Buatan, 2025)
In the digital era, data security is essential for preventing unwanted access to information. To improve message security, this study intends to apply a mixture of three cryptographic algorithms: RSA, Vigenere cipher, and permutation cipher. The Vigenere and permutation ciphers are used to the message content to add an extra degree of security, while the RSA technique is utilized for asymmetric key encryption. In this system, the Vigenere cipher and permutation cipher, is used to encrypt the message, followed by RSA is used to encrypt the Vigenere process key. According to test results, combining these three techniques strengthens the cryptographic defenses against frequency analysis and brute force assaults by increasing their complexity. Although the combination lengthens the processing time, the resulting security is higher than the application of a single method. This system is expected to be applied to applications that require the protection of sensitive data with a high level of security.